The Road from Emergency Employment towards Integrated Rural Access : Re-orientation of the Afghanistan National Emergency Employment Program to the Rural Access Program - World Bank (Washington, DC, 2014)
This paper provides an institutional record of the implementation experiences of all the four World Bank-assisted National Emergency Employment Program (NEEP)/National Rural Access Program (NRAP) projects and evaluates the impact on community members of the improved rural access that the projects have provided. It is based on desk reviews of project documentation, supervision mission notes, field visits to communities in rural areas, and detailed discussions with project team members and staff involved in implementation based in Afghanistan. Chapter two describes the program's evolving objectives, structure, and implementation arrangements. Chapter three evaluates NEEP's record in providing a social safety net, and chapter four describes the arrangements for community participation in program decision making and the perceptions of community members about the program's benefits. Chapter five describes the Reintegration and Alternative Livelihoods Program (NEEP-RAL), which has a similar theme to those of the other NEEP projects, but different dynamics and implementation arrangements from them. Chapter six reviews key findings and lessons learned, and finally, chapter seven concludes.